Passive Peritoneal Drainage Impact on Fluid Balance and Inflammatory Mediators: A Randomized Pilot Study. Issue 2 (March 2020) - Pourmoghadam, Kamal K.; Kubovec, Stacey; DeCampli, William M.; Khallouq, Bertha Ben; Piggott, Kurt; Blanco, Carlos; Fakioglu, Harun; Kube, Alicia; Narasimhulu, Sukumar Suguna
Background: Infants after cardiopulmonary bypass are exposed to increasing inflammatory mediator release and are at risk of developing fluid overload. The aim of this pilot study was to evaluate the impact of passive peritoneal drainage on achieving negative fluid balance and its ability to dispose of inflammatory cytokines. Methods: From September 2014 to November 2016, infants undergoing STAT category 3, 4, and 5 operations were randomized to receive or not receive intraoperative prophylactic peritoneal drain. We analyzed time to negative fluid balance and perioperative variables for each group. Pro- and anti-inflammatory cytokines were measured from serum and peritoneal fluid in the passive peritoneal drainage group and serum in the control group postoperatively. Results: Infants were randomized to prophylactic passive peritoneal drain group (n = 13) and control (n = 12). The groups were not significantly different in pre- and postoperative peak lactate levels, postoperative length of stay, and mortality. Peritoneal drain patients reached time to negative fluid balance at a median of 1.42 days (interquartile range [IQR]: 1.00-2.91), whereas the control at 3.08 (IQR: 1.67-3.88; P = .043). Peritoneal drain patients had lower diuretic index at 72 hours, median of 2.86 (IQR: 1.21-4.94) versus 6.27 (IQR: 4.75-11.11; P = .006). Consistently, tumor necrosis factor-α, interleukin (IL)-4, IL-6, IL-8, IL-10, and interferon-γ were present at higher levels in peritoneal fluid than serum at 24 and 72 hours. However, serum cytokine levels in peritoneal drain and control group, at 24 and 72 hours postoperatively, did not differ significantly. Conclusions: The prophylactic passive peritoneal drain patients reached negative fluid balance earlier and used less diuretic in early postoperative period. The serum cytokine levels did not differ significantly between groups at 24 and 72 hours postoperatively. However, there was no significant difference in mortality and postoperative length of stay.